ANALISIS PENERAPAN METODE ACTIVITY BASED COSTING DALAM PENENTUAN HARGA POKOK KAMAR PADA ROUGE LOUNGE BAR, VILLAS & SPA TAHUN 2019 - Dewi Ni Wayan Septya (UNHI Press, 2022)
This study aims to contribute in determining the appropriate and accurate hotel rooms cost using activity based costing method at Rouge Lounge Bar, Villas & Spa. The technique in the data analysis used in this research is comparative descriptive quantitative analysis by applying activity-based costing method.The results of this study indicate that that there is difference between the calculation of the room cost using Activity Based Costing method and the method used by the management. The Activity Based Costing method developed smaller result of room cost calculation than the price calculation set by the management. The price difference for Deluxe room is in the amount of Rp. 576. 797 while for the Family rooms is in the amount of Rp. 636. 788. The price difference is caused by the imposition of overhead costs on each type of room used by the management using only single cost driver, this caused distortion cost. Meanwhile in the Activity-Based Costing method, the imposition of overhead costs to each product applies multiple cost drivers in accordance with the product consumption guidelines. Therefore, the ABC System is able to allocate activity costs appropriately based on the consumption of each activity.